Acute Bacterial Meningitis Among Children under Five Years of Age in Baghdad. - Al-Rawazq, Huda S. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The periodic review conducted of acute bacterial meningitis in children younger than 5 years of age in Baghdad to reflect changes in the epidemiological pattern of this infection. Patients and Methods: Sixty patients with signs and symptoms suggestive of meningitis who were admitted to Central Teaching Hospital in Baghdad City were included in a prospective study started from the 1st October till the 30th of December 2009. By bacteriological study, biochemical and cytological study in the laboratory, WBCs in the blood with differential count was done to support the diagnosis of bacterial meningitis.Results: Present study revealed that from (60) patients (6) cases (10.0 %) showed positive and (54) cases (90.0 %) negative cultures to CSF patients.Conclusions: The administration of antibiotic before lumber puncture associated with false negative CSF culture. Most cases of meningitis were under one year of age occurred in male more than female with bottle feeding. Fever was the most common presenting symptom followed by vomiting and convulsion.